Evaluasi Pengelolaan Dana Desa di Kelurahan Banjarsari Kecamatan Metro Utara Lampung - Ria Dika Rahmawati; Karnila Ali; Nani Septiana (Jurnal Manajemen DIVERSIFIKASI, 2026)
The government is responsible for managing state finances, including central, regional and village finances. Considering that the state disburses large amounts of village funds every year to support villages, through the State Revenue and Expenditure Budget (APBN), managing village funds in the field of community empowerment is crucial. Details of the budget that are not published to the general public are an indication of lack of transparency in government governance practices. Based on a survey conducted by researchers in Banjarsari sub-district, North Metro, Metro City, there are problems involving an imbalance between budget allocation and the need for improvements to facilities and infrastructure. Apart from that, Banjarsari Subdistrict is lagging behind in infrastructure development when compared to other subdistricts in Metro City. This research uses analytical research methods with a quantitative approach, showing that the efficiency of financial management is currently below 40%. There are limitations in the allocation of village funds and transfer income which has an impact on reducing effectiveness in implementing development programs and community services in the Banjarsari sub-district